Customer Engagement in the Digital Age - Supriadi, Asep (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research explores the factors that influence customer engagement in the digital era, with a focus on digital service quality, activity on social media, user experience, personalization of content, responsiveness and speed of service, and adoption of interactive features. Through systematic literature analysis, research findings show that these factors have a significant impact on customer engagement levels. Companies that are able to pay attention to and optimize these aspects in their marketing and customer relationship strategies tend to achieve higher customer engagement. The practical implication of this research is that it is important for companies to prioritize providing satisfying and relevant customer experiences in an ever-evolving digital environment. Additionally, there is still room for further research in understanding the dynamics of customer engagement in an ever-changing digital context.